THE INFLUENCE OF E-SERVICE QUALITY, EASINESS, TRUST OF QUALITY OF INFORMATION, AND SALES PROMOTION ON PURCHASE DECISIONS ON THE TRAVELOKA APPLICATION - Diana Azzahra; Yanuar Firdaus Arie Wibowo; Cholid Fauzi (STKIP PGRI Tulungagung, 2025)
This research aims to analyze the influence of E-Service Quality, Easiness, Trust in Quality of Information, and Sales Promotion on consumer Purchase Decisions in the Traveloka application. This research also considers whether electronic service quality (E-Service Quality) is a dominant factor in digitizing the Traveloka Online Travel Agent (OTA). The research uses a quantitative approach by applying PLS-SEM (Partial Least Squares Structural Equation Modeling) to analyze complex relationships between variables and validate the reliability and validity of the constructs involved. Data was collected through an online survey distributed via social media to 385 samples with certain criteria, and analysis was carried out on measurement models, structural models, and hypotheses. The research results show that although E-Service Quality, Easiness, Trust in Quality of Information, and Sales Promotion do not have a significant positive effect on purchasing decisions, the ease of use of the Traveloka application significantly increases consumer confidence in the quality of the information provided. Thus, this research makes an important contribution to understanding the factors that influence consumer behavior in the context of the Traveloka application.